Análise sistêmica das massas de tamponamento para altos-fornos - Ribeiro, Aloísio Simões (2010)
The increase in the world steel production mainly observed in the last decade demanded a significant growth in the hot metal production through the blast furnace process. A key point in blast furnaces operation is related to the taphole mix used to plug the hole that is where the tapping is carried out. The taphole mix is a key aspect for the production flow of integrated mills because, in the blast furnaces, it is responsible to maintain a stable tapping, ensuring the supply of hot metal to the steelmaking, maintaining all stages of the crude steel plants in synchrony. The taphole mixes for blast furnace are very special products in the broad universe of refractory materials due to its complex chemistry composition, being applied in extreme conditions of temperature and demand. In this context, the literature and the technical aspects related to taphole mixes require a more comprehensive technical contribution, considering the influence of some additives on their properties. The aim of this work is to evaluate the influence of different raw materials and additives on the properties of taphole mixes related to their densification, adhesion and usinability features. The results of the tests were assessed according to the AHP (Analytical Hierarchy Process) method, which allows for the selection of the best formulation considering all the parameters involved.